2021
DOI: 10.1002/celc.202101023
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Activity Produced from Abundant Expression of C‐Type Cytochromes in a Filamentous Gram‐Positive Bacterium

Abstract: Natural microbes employing c-type cytochromes (c-Cyts) for extracellular electron transport (EET) were greatly valuable to develop redox-based bioelectrochemical applications. However, low levels of c-Cyt expression limited the phylogenetically diverse Gram-positive species to be used in bioelectrochemical devices. This work reported the remarkable finding that a high level of c-Cyts was expressed in the cells of the Gram-positive strain Lysinibacillus varians GY32. c-Cyts in Lysinibacillus varians GY32 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Assuming the redox potential of the cysteine/cystine couple in the anodic culture was −40 mV, it would be thermodynamically favorable to deliver electrons from many redox proteins or coenzymes to the anode ( 41 ). Our recent results showed that the membrane-bound c -type cytochromes of GY32 have a midpotential of −178 mV ( 43 ). Therefore, the cysteine/cystine couple may be reduced by these c -type cytochromes in strain GY32.…”
Section: Resultsmentioning
confidence: 99%
“…Assuming the redox potential of the cysteine/cystine couple in the anodic culture was −40 mV, it would be thermodynamically favorable to deliver electrons from many redox proteins or coenzymes to the anode ( 41 ). Our recent results showed that the membrane-bound c -type cytochromes of GY32 have a midpotential of −178 mV ( 43 ). Therefore, the cysteine/cystine couple may be reduced by these c -type cytochromes in strain GY32.…”
Section: Resultsmentioning
confidence: 99%